LapOntoSPM - an ontology for laparoscopic surgeries and its application to surgical phase recognition - Katić, Darko; Julliard, Chantal; Wekerle, Anna-Laura; Kenngott, Hannes Götz; Müller, Beat P.; Dillmann, Rüdiger; Speidel, Stefanie; Jannin, Pierre; Gibaud, Bernard (International journal of computer assisted radiology and surgery, 2015)
The rise of intraoperative information threatens to outpace our abilities to process it. Context-aware systems, filtering information to automatically adapt to the current needs of the surgeon, are necessary to fully profit from computerized surgery. To attain context awareness, representation of medical knowledge is crucial. However, most existing systems do not represent knowledge in a reusable way, hindering also reuse of data. Our purpose is therefore to make our computational models of medical knowledge sharable, extensible and interoperational with established knowledge representations in the form of the LapOntoSPM ontology. To show its usefulness, we apply it to situation interpretation, i.e., the recognition of surgical phases based on surgical activities.
Gesehen am 07.05.2020